2013
DOI: 10.1002/chem.201301294
|View full text |Cite
|
Sign up to set email alerts
|

Acenaphthylene‐Fused Cyclo[8]pyrroles with Intense Near‐IR‐Region Absorption Bands

Abstract: An acenaphthylene-fused cyclo[8]pyrrole was synthesized by using an oxidative coupling reaction of the corresponding 2,2'-bipyrrole. Two conformational isomers 1 a and 1 b were isolated, and their molecular structures were elucidated by X-ray crystallographic studies. The less-polar and lower-symmetry 1 b isomer can be converted into the 1 a isomer through a thermal ring flip. Application of the perimeter model developed by Michl to magnetic circular dichroism spectroscopic data and theoretical calculations de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 25 publications
(54 reference statements)
3
36
0
Order By: Relevance
“…It was found that, starting from compound 2, the HLG could be progressively reduced by structural elaboration of the acceptor end of the fused pyrrole. Switching off the acceptor functionality by reduction of the amide groups was also considered (compound 1), and was indeed predicted to result in a broadened HLG (3.81 eV), comparable with those calculated for reported electron-rich systems, the unsubstituted acenaphthopyrrole 49−53 and its 2,5-di-tert-butyl derivative 54 (3.89 and 3.97 eV, respectively, at the same level of theory). In 2, the KS bandgap (3.70 eV) is comparable with that predicted for 3,4-dichloroacenaphthopyrrole 53,55 (3.64 eV).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…It was found that, starting from compound 2, the HLG could be progressively reduced by structural elaboration of the acceptor end of the fused pyrrole. Switching off the acceptor functionality by reduction of the amide groups was also considered (compound 1), and was indeed predicted to result in a broadened HLG (3.81 eV), comparable with those calculated for reported electron-rich systems, the unsubstituted acenaphthopyrrole 49−53 and its 2,5-di-tert-butyl derivative 54 (3.89 and 3.97 eV, respectively, at the same level of theory). In 2, the KS bandgap (3.70 eV) is comparable with that predicted for 3,4-dichloroacenaphthopyrrole 53,55 (3.64 eV).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…Dibromopyrrole 1 was prepared via protection of the NH moiety of acenaphtho­[1,2- c ]­pyrrole by treatment with n -BuLi and ethyl chloroformate, followed by bromination with NBS. Pyrrole 2 was prepared via the Miyaura–Ishiyama borylation of iodopyrrole in 63% yield. Terpyrrole 3 was obtained via the Suzuki–Miyaura cross-coupling of 1 with 2 .…”
mentioning
confidence: 99%
“…In order to increase the solubility of the target acenaphtho derivatives in common organic solvents, two tert -butyl groups were introduced into acenaphthylene, and the resulting compound was converted to ethylacenaphtho[1,2- c ]pyrrole-1-carboxylate 2. 18 Formylation of 2 with the Vilsmeier reagent gave α-formylated compound 3a in 98% yield ( Scheme 1 ). The formyl group of 3a was converted to an acetoxymethyl group by reduction with NaBH 4 followed by acetylation with Ac 2 O and 4-dimethylaminopyridine (DMAP).…”
Section: Resultsmentioning
confidence: 99%
“…POCl 3 (1.9 mL, 23.6 mmol) was added to dry DMF (2.2 mL, 24.5 mmol) at 0 °C under an argon atmosphere, and the mixture was stirred at rt for 30 min. After acenaphthopyrrole 2 ( ref. 18 ) (6.22 g, 16.6 mmol) in dry CH 2 Cl 2 (115 mL) was added at rt, the mixture was stirred for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation